Sequence-specific DNA binding activity of the cross-brace zinc finger motif of the piggyBac transposase - Morellet, Nelly (Nucleic Acids Res, 2018)
The piggyBac transposase (PB) is distinguished by its activity and utility in genome engineering, especially in humans where it has highly promising therapeutic potential. Little is known, however, about the structure–function relationships of the different domains of PB. Here, we demonstrate in vitro and in vivo that its C-terminal Cysteine-Rich Domain (CRD) is essential for DNA breakage, joining and transposition and that it binds to specific DNA sequences in the left and right transposon ends, and to an additional unexpectedly internal site at the left end. Using NMR, we show that the CRD adopts the specific fold of the cross-brace zinc finger protein family. We determine the interaction interfaces between the CRD and its target, the 5′-TGCGT-3′/3′-ACGCA-5′ motifs found in the left, left internal and right transposon ends, and use NMR results to propose docking models for the complex, which are consistent with our site-directed mutagenesis data. Our results provide support for a model of the PB/DNA interactions in the context of the transpososome, which will be useful for the rational design of PB mutants with increased activity.